Before the Celtic Tiger: change without modernisation in Ireland 1959-1989 - Girvin, Brian (Economic & Social Studies, 2010)
This paper engages with and expands on a number of themes examined in Tom Garvin?s Preventing the Future. It asks if it is accurate to describe independent Ireland as poor before 1950, arguing that Ireland became poor in comparative terms only during the 1950s. While agreeing with the view that Ireland changed during the 1960s, the main contention of this article is that modernisation was severely constrained between 1959 and 1989 by the continuing dominance of traditional interests and attitudes. It also argues that Ireland?s poor economic performance was a consequence of this continuity as successive governments, privileged property owners and rural interests dominated other sectors of society. It suggests that the importance of culture and continuity in the process of change has often been underestimated and this requires closer attention if specific outcomes are to be explained in a satisfactory fashion.
Keywords: Modernisation; Ireland; Economic performance; Social change